The best method leading to excellent teamwork in organization according to employees perspective / Mohd Hairul Abdul Rahman - Abdul Rahman, Mohd Hairul (2009)
Today management must be more creative and innovative in meeting the challenges of declining productivity. Increasing foreign competition and a work force that may not be motivate by traditional management practices. Employee involvement is one approach to improving the quality and productivity with cooperative relationships, open communication, and group problem solving and decision-making. This approach received substantial credit for contributing to a quality and productivity improvement in a number of countries. Participation and employee involvement have also been successful in the United States in both manufacturing and service industries. Several types of employees groups may characterize the participative process. Some of the most common terms are quality circles, quality improvement teams, productivity teams, and employee involvement groups. There are also idea groups, winner's circles, and progress groups that reflect specific needs and organizational culture. In all cases, there are groups of employees who volunteer to be trained in problem-solving techniques and who have the improvement of quality and productivity within organization as their primary goal.